Review of “Taxonomic revision of the genus Dioon (Zamiaceae)” published in Phytotaxa 442(4): 267–290 - Haynes, Jody L. (Phytotaxa, 2020)
Dioon Lindley (1843: 59–60) is the best understood of the three cycad genera in Mesoamerica. As such, the appearance of an article published earlier this year in Phytotaxa, claiming to be a revision of the genus, was somewhat surprising. While the article provides a fairly thorough summary of previous work, there is no taxonomic revision. There are also numerous issues/errors (some quite serious) that need to be clarified and/or corrected (see separate Appendix for full list). This correspondence will critique the aforementioned article section by section, beginning with the title and stated goals.